2007
DOI: 10.1186/1751-0147-49-38
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral sodium acetate administration on plasma acetate concentration and acid-base state in horses

Abstract: Aim: Sodium acetate (NaAcetate) has received some attention as an alkalinizing agent and possible alternative energy source for the horse, however the effects of oral administration remain largely unknown. The present study used the physicochemical approach to characterize the changes in acid-base status occurring after oral NaAcetate/acetic acid (NAA) administration in horses.Methods: Jugular venous blood was sampled from 9 exercise-conditioned horses on 2 separate occasions, at rest and for 24 h following a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…In the present study, no clear effect of the F diet on performance was observed, but there was a lowering of postexercise plasma lactate concentration, confirming previous findings for a high-fibre diet (Palmgren-Karlsson et al, 2002). Waller and Lindinger (2007) reported profound plasma alkalosis, that is, a decrease in venous plasma hydrogen concentration and an increase in plasma TCO 2 and HCO 3 2 , after post-exercise oral administration of sodium acetate. These results were confirmed in the present study, where venous pH, TCO 2 and HCO 3 2 concentrations were higher in horses on the F diet.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no clear effect of the F diet on performance was observed, but there was a lowering of postexercise plasma lactate concentration, confirming previous findings for a high-fibre diet (Palmgren-Karlsson et al, 2002). Waller and Lindinger (2007) reported profound plasma alkalosis, that is, a decrease in venous plasma hydrogen concentration and an increase in plasma TCO 2 and HCO 3 2 , after post-exercise oral administration of sodium acetate. These results were confirmed in the present study, where venous pH, TCO 2 and HCO 3 2 concentrations were higher in horses on the F diet.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the acetate solution resulted in substantial osmotic and acid–base disturbances owing to its large sodium load (see Waller & Lindinger, 2007), which probably led to the tendency for decreased muscle H 2 O content at 4 h of recovery in the acetate treatment. This intracellular dehydration may have contributed to decreasing the rate of glycogen resynthesis in the acetate treatment, as has been suggested previously in horses (Waller et al 2009), humans (Keller et al 2003) and rats (Low et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…After absorption in the intestine, the acetate present in the enteral electrolyte solutions is metabolized by the liver and skeletal muscle, where it is converted to acetyl-CoA that enters the cycle and respiratory chain resulting in the consumption of H + ions and consequent production of H 2 O and un-buffered HCO 3 -, so it has an alkalinizing action without changing the pH of the intestinal lumen (KREBS, 1954;PATRA et al, 1982;SEN et al, 2009;WALLER& LINDINGER, 2007;WALLER et al, 2009). The results of the present study agreed with WALLER &LINDINGER (2007) andSEN et al (2009) who observed in calves and adult horses, respectively, that sodium acetate is an efficient alkalinize agent that can be utilized in enteral electrolytes solutions alternatively to sodium bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…The use of enteral solutions containing sodium acetate can be an alternative to sodium bicarbonate for the correction of acidosis in sick foals. Sodium acetate metabolism generates the consumption of hydrogen ions in the liver and muscle, without interfering with the pH of the intestinal lumen, making it more suitable for enteral electrolyte solutions compared to sodium bicarbonate (MARSHALL et al, 2008) in calves and horses with acidosis (NAyLOR& FORSyTH, 1986;PETHICK et al, 1993;SEN et al, 2009;WALLER& LINDINGER, 2007;WALLER et al, 2009).…”
Section: Introductionmentioning
confidence: 99%